Characterisation of the wildlife reservoir community for human and animal trypanosomiasis in the Luangwa Valley, Zambia - Anderson, N.E.; Mubanga, J.; Fèvre, Eric M.; Picozzi, K.; Eisler, M.C.; Thomas, R. (Public Library of Science, 2011)
Animal and human trypanosomiasis are constraints to both animal and human health in Sub-Saharan Africa, but there is little recent evidence as to how these parasites circulate in wild hosts in natural ecosystems. The Luangwa Valley in Zambia supports high densities of tsetse flies (Glossina species) and is recognised as an historical sleeping sickness focus. The objective of this study was to characterise the nature of the reservoir community for trypanosomiasis in the absence of influence from domesticated hosts.